Enhancing Students’ Speaking Through Questions Game Of The Senior High School Of Sanggar Kegiatan Belajar Kota Bekasi - Windarni, Natalia Hardayanti Cahya; Solo, Lenny; Hidayati, Dini (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Cahyawindarni, Natalia Hardayanti. ENHANCING STUDENTS’ SPEAKING THROUGH QUESTIONS GAME OF THE SENIOR HIGH SCHOOL OF SANGGAR KEGIATAN BELAJAR KOTA BEKASI(2024)Skripsi.Jakarta:. English Language Education Study Program, Pancasakti University.2024. The objective of research is to study effect the students’ poor performance in speaking English . It was consisted of the class of 22 students in Paket C Sanggar Kegiatan Belajar Kota Bekasi in academic year of 2023/2024. The research of this study was conducted by using classroom action research. The data used in this research were quantitative and qualitative data and the instruments of collecting data were used such as Pre-Test and Post-test, interview sheet, observation and photography. The quantitative data were taken from the test. The test was given to the students in from of pre-test, post test in Cycle 1 and Post Test in Cycle 2. Both internal and external forces are involved, according to the findings of the observation and interview. Internal psychological factors include low motivation, anxiety of making a mistake, and a lack of confidence in one's ability to speak English. The primary cause is poor speech, grammar, and vocabulary. The second external factor is the absence of spoken English and the application of the central teacher technique. The study's findings showed that students' use of question games improved their learning outcomes. Two cycles are used to implement the game. There are four components to every cycle: planning, action, observation, and reflection. The learning activity was improved with the inclusion of Cycles 1 and 2. Question games can help students improve their speaking abilities in two ways. The first was that question games could make pupils less bored, and the second was that they could encourage them to learn English.